Cross-curricular Issues and Published ELT Materials in Spain - Rascón-Moreno, Diego (Miscelánea: A Journal of English and American Studies, 2014)
This paper shows the results of examining up to forty-six sets of published ELT materials borrowed from primary and secondary schools of the Spanish city of Jaén in order to know how the eight cross-curricular issues encouraged by educational policies are addressed in them. These topics should be introduced in the English classroom so that the full development of the student’s personality can be achieved. Not only a general descriptive analysis of all the data gathered is included here, but also a specific one consisting in determining whether the variables of publishing house, level and educational cycle make results vary significantly –for which the ANOVA Test was used. A relevant conclusion of this study is that the value-laden topics under research are relatively often addressed in the materials sampled, but that their teaching is poor in terms of width of coverage because only some of the contents about them that should be covered according to the official guidelines are dealt with. Concerning the specific analysis, the main idea that can be derived is that the variable of publishing house rarely affects results, as against the level and educational cycle of these resources, which usually yield statistically significant differences.